Loss of cardiac mitochondrial complex I persulfidation impairs NAD+ homeostasis in aging - Drekolia, Maria-Kyriaki; Karantanou, Christina; Wittig, Ilka; Li, Yuanyuan; Fuhrmann, Dominik C.; Brüne, Bernhard; Katsouda, Antonia; Hu, Jiong; Papapetropoulos, Andreas; Bibli, Sofia-Iris (Redox Biology, 2024)
Protein persulfidation is a significant post-translational modification that involves addition of a sulfur atom to the cysteine thiol group and is facilitated by sulfide species. Persulfidation targets reactive cysteine residues within proteins, influencing their structure and/or function across various biological systems. This modification is evolutionarily conserved and plays a crucial role in preventing irreversible cysteine overoxidation, a process that becomes prominent with aging. While, persulfidation decreases with age, its levels in the aged heart and the functional implications of such a reduction in cardiac metabolism remain unknown. Here we interrogated the cardiac persulfydome in wild-type adult mice and age-matched mice lacking the two sulfide generating enzymes, namely cystathionine gamma lyase (CSE) and 3-mercaptopyruvate sulfurtransferase (3MST). Our findings revealed that cardiac persulfidated proteins in wild type hearts are less abundant compared to those in other organs, with a primary involvement in mitochondrial metabolic processes. We further focused on one specific target, NDUFB7, which undergoes persulfidation by both CSE and 3MST derived sulfide species. In particular, persulfidation of cysteines C80 and C90 in NDUFB7 protects the protein from overoxidation and maintains the complex I activity in cardiomyocytes. As the heart ages, the levels of CSE and 3MST in cardiomyocytes decline, leading to reduced NDUFB7 persulfidation and increased cardiac NADH/NAD+ ratio. Collectively, our data provide compelling evidence for a direct link between cardiac persulfidation and mitochondrial complex I activity, which is compromised in aging.